(untitled) (Revista Educação, Artes e Inclusão, 2023)
This text is an experience report on the artistic production entitled Subjective Self-portrait, adapted to the context of education in remote format, due to the COVID pandemic19. This artistic practice was proposed to students of the 1st year of the Licentiate Degree in Visual Arts, in the discipline of Painting I, as an assessment instrument. Its objective is to present the Painting Discipline I, of a practical/presential nature, in a remote format, which was adapted, overcoming the barriers of physical distance. In this way, it offered academics a qualified training process until the discipline can return in the classroom format. It is a qualitative research, in the period from March to May 2020. The theoretical support used is Suassuna (2011), Bachelard (2000), Lagnado (1994), Silva (2008), Linhares; Laurel; Alcantara (2017) among others. The artistic production of the Subjective Self-portrait presented satisfactory results, even in a remote format, in which the academics were able to complete the production, based on reflections on their moral and ethical values, their anxieties in relation to the Licentiate Degree in Visual Arts, becoming a viable instrument for the present moment.